Dampak Penggunaan Bahasa Daerah terhadap Pembelajaran Bahasa Indonesia di SMKN 1 Loksado - Misna (Zona Education Indonesia, 2025)
This study aims to analyze the impact of the use of regional languages in daily life on Indonesian language learning at SMKN 1 Loksado. In a multilingual environment such as Loksado, where regional languages such as Meratus and Banjar are predominantly spoken, there is a shift in students' attitudes and understanding of Indonesian. The method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the intensive use of regional languages affects students' ability to speak Indonesian, both in terms of vocabulary, sentence structure, and pronunciation. Although regional languages enrich local culture, a balanced pedagogical approach is needed so that students are still able to master Indonesian properly and correctly